A novel approach for measuring resistance of Escherichia coli and Listeria monocytogenes to hydrogen peroxide using label-free magnetic resonance imaging and relaxometry. (April 2015) - Le, Phuong; Zhang, Lu; Lim, Victor; McCarthy, Michael J.; Nitin, Nitin
Abstract: Sanitation is a critical step to reduce microbial load in many process industries. To assess and monitor the efficacy of sanitation processes, there is a need to rapidly measure microbial resistance to sanitizers and determine the critical concentration of sanitizers above which significant reduction in microbial load can be achieved in a complex environment. In this study, a rapid and label-free magnetic resonance (MR) imaging and relaxometry method was developed to measure resistance of Escherichia coli and Listeria monocytogenes to hydrogen peroxide based on the activity of intracellular catalase enzymes. Intracellular catalase activity is a measure of resistance of bacteria to hydrogen peroxide as these enzymes can degrade hydrogen peroxide to oxygen and water. Using sub-lethal and lethal concentration of hydrogen peroxide, the resistance of both the exponential and stationary growth phase E. coli suspended in PBS and in high organic content solution was characterized. The results show that in stationary growth phase E. coli, molecular oxygen, generated by the interaction of endogenous catalases with 1% H2 O2, results in an 8 fold increase in MR imaging signal intensity and a 22 fold decrease in spin-lattice relaxation time (T1 ) compared to the controls. Furthermore, the resistance of E. coli and L. monocytogenes to H2 O2, measured using the MR method, was correlated with the bacterial reduction, quantified with traditional plate counting method. The comparison between the two methods shows the MR method developed in this study can determine the critical concentration of H2 O2 above which a significant reduction in bacterial culturability (at least 4 logs) was achieved. Overall, this study demonstrates the potential of MR imaging and relaxometry method to predict the efficacy of H2 O2 in high organic load environment. Highlights: MR method to assess oxidative stress resistance of E. coli and Listeria monocytogenes to H2 O2 . Oxidative stress resistance of bacteria can assess reduction in bacterial load. Resistance to oxidative stress is a function of physiological state of bacteria. Bacterial response to H2 O2 can be detected in samples with high organic content.